Perbedaan Produktivitas Usahatani Padi Sawah antara Sistem Bagi Hasil dengan Lahan Milik Sendiri di Desa Pudonggala Kecamatan Sawa Kabupaten Konawe Utara - Purnasari, Irma; Budiyanto, Budiyanto; Yusria, Wa Ode (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This research was conducted in Pudonggala Village, Sawa Sub-district of North Konawe Regency from May until July 2017. This study was aimed to determine the value of productivity obtained by each paddy farmer namely between owner farmers and tenant farmer, and to analyze the differences in productivity of paddy farming between owner farmer and tenant farmer. Data were collected through observation, interview using questionnaire, and recording. Data analysis was used in this research is independent sample t-test. The results showed that in wetland paddy farming in Pudonggala Village, Sawa Sub-district of North Konawe Regency the average production of paddy in profit sharing system had equal to 3.081 kg with average productivity equal to 3.627 kg/ha. While average production of paddy in oned land had equal to 5,081 kg with average productivity equal to 3,745 kg/ha. In addition, the result of independent sample t-test shows that the productivity variable had at-value of 2,254. This t-value was bigger than the value of t-table at the 95% of confidence level namely 1,711, which means that there was a significant difference of productivity of wetland paddy between profit sharing systems with owned land.